DIDACTIC CONDITIONS OF WORKING ON PHRASES IN SPEECH DEVELOPMENT OF PRIMARY CLASS STUDENTS - Turaeva Sanobar Sulaymonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Idioms play an incomparable role in the quality and interesting organization of mother tongue education in primary grades. Phrases can increase the interest of young students in the language. Because the colorfulness and imagery in the expressions attract the reader's attention. It is necessary to systematically organize work on phrases in the classes of mother tongue and reading literacy. The effectiveness and liveliness of the student's speech are determined by the appropriate use of language tools in the speech.